Pulse wave velocity distribution in a cohort study. Issue 7 (July 2015) - Cunha, Pedro G.; Cotter, Jorge; Oliveira, Pedro; Vila, Isabel; Boutouyrie, Pierre; Laurent, Stéphane; Nilsson, Peter M.; Scuteri, Angelo; Sousa, Nuno
<x xml:space="preserve">Abstract</x> Background: By contrast with other southern European people, north Portuguese population registers an especially high prevalence of hypertension and stroke incidence. We designed a cohort study to identify individuals presenting accelerated and premature arterial aging in the Portuguese population. Method: Pulse wave velocity (PWV) was measured in randomly sampled population dwellers aged 18–96 years from northern Portugal, and used as a marker of early vascular aging (EVA). Of the 3038 individuals enrolled, 2542 completed the evaluation. Results: Mean PWV value for the entire population was 8.4 m/s (men: 8.6 m/s; women: 8.2 m/s; P < 0.02). The individuals were classified with EVA if their PWV was at least 97.5th percentile of z-score for mean PWV values adjusted for age (using normal European reference values as comparators). The overall prevalence of EVA was 12.5%; 26.1% of individuals below 30 years presented this feature and 40.2% of individuals in that same age strata were placed above the 90th percentile of PWV; and 18.7% of the population exhibited PWV values above 10 m/s, with male predominance (17.2% of men aged 40–49 years had PWV > 10 m/s). Logistic regression models indicated gender differences concerning the risk of developing large artery damage, with women having the same odds of PWV above 10 m/s 10 years later than men. Conclusion: The population PWV values were higher than expected in a low cardiovascular risk area (Portugal). High prevalence rates of EVA and noteworthy large artery damage in young ages were found.